The role of volleyball extracurricular on student discipline - Asep Angga Permadi; Shohibul Iman; Irwan Hermawan; Mohd Izwan Shahril; Taufiq Hidayat (Journal Of Sport Education (JOPE), 2023)
(English)This study aims to determine the role of volleyball extracurriculars on student discipline, especially at SMK Bhakti Putra. This research was conducted by distributing questionnaires to 30 students of volleyball extracurricular at SMK Bhakti Putra. In addition to other techniques, namely observation and documentation. In general, this research was conducted using quantitative research methods with an ex post facto research design is a statistic used to analyze data by describing or describing the data that has been collected as it is without intending to make conclusions that apply to the public or generalizations. Based on the calculation results, it can be concluded that for the validity test, there are 45 valid statement items for the X variable and 38 accurate statement items for the Y variable, while the X variable reliability test is 0.924 and the Y variable is 0.882. The results of hypothesis testing indicate that the proposed hypothesis can be accepted because the value of the R count is more significant than the R table, namely 0.782 > 0.361. After going through several stages of the previous calculation, it can be concluded that volleyball extracurricular plays a role in student discipline attitude by 61.1% while the role from outside is 38.9%. From the results of the study, it can be concluded that extracurricular volleyball plays an important role in shaping students' disciplinary attitudes at SMK Bhakti Putra. This shows that extracurricular activities can be an important factor in shaping the character and positive attitudes of students at school. As a recommendation for future research, it is necessary to conduct research with different designs such as experimental with a larger number of samples, consider family and social environmental factors, use interview or direct observation data collection techniques, and encourage the improvement of extracurricular programmes in schools to positively shape students' disciplinary attitudes (Indonesian)Penelitian ini bertujuan untuk mengetahui peranan ekstrakurikuler bola voli terhadap disiplin siswa khususnya di SMK Bhakti Putra. Penelitian ini dilakukan dengan menyebarkan kuesioner kepada 30 siswa ekstrakurikuler bola voli di SMK Bhakti Putra. Selain teknik lain yaitu observasi dan dokumentasi. Secara umum penelitian ini dilakukan dengan menggunakan metode penelitian kuantitatif dengan desain penelitian ex post facto, statistik yang digunakan untuk menganalisis data dengan cara mendeskripsikan atau mendeskripsikan data yang telah terkumpul sebagaimana adanya tanpa bermaksud membuat kesimpulan yang berlaku umum atau generalisasi. Berdasarkan hasil perhitungan dapat disimpulkan bahwa untuk uji validitas terdapat 45 butir pernyataan yang valid untuk variabel X dan 38 butir pernyataan akurat untuk variabel Y, sedangkan uji reliabilitas variabel X sebesar 0,924 dan variabel Y sebesar 0,882 . Hasil pengujian hipotesis menunjukkan bahwa hipotesis yang diajukan dapat diterima karena nilai R hitung lebih signifikan dari R tabel yaitu 0,782 > 0,361. Setelah melalui beberapa tahapan perhitungan sebelumnya, dapat disimpulkan bahwa ekstrakurikuler bola voli berperan terhadap sikap disiplin siswa sebesar 61,1% sedangkan peran dari luar sebesar 38,9%. Dari hasil penelitian, dapat disimpulkan bahwa ekstrakurikuler bola voli berperan penting dalam membentuk sikap disiplin siswa di SMK Bhakti Putra. Hal ini menunjukkan bahwa kegiatan ekstrakurikuler dapat menjadi faktor penting dalam membentuk karakter dan sikap positif siswa di sekolah. Sebagai rekomendasi penelitian selanjutnya, perlu dilakukan penelitian dengan desain yang berbeda seperti eksperimental dengan jumlah sampel lebih banyak, mempertimbangkan faktor lingkungan keluarga dan sosial, menggunakan teknik pengumpulan data wawancara atau pengamatan langsung, serta mendorong peningkatan program ekstrakurikuler di sekolah untuk membentuk sikap disiplin siswa secara positif.  Copyright © The Author (s) 2023Journal of Sport Education (JOPE) is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.